2010
DOI: 10.3102/0013189x10383560
|View full text |Cite
|
Sign up to set email alerts
|

Using Growth for Accountability

Abstract: Growth-based approaches to federal accountability are receiving considerable attention because they have the potential to reward schools and teachers for improving student performance over time by measuring student progress at all levels of the performance spectrum, including progress by students who have not reached proficiency on state accountability assessments. The use of growth in accountability holds promise for students with disabilities, but measuring changes over time in academic performance with larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…Many researchers have noted concerns with value-added models for evaluating special education teachers in general (Buzick & Laitusis, 2010;Goe, Bell, & Little, 2008;Steinbrecher, Selig, Cosbey, & Thorstensen, 2014). This is particularly problematic for teachers of students with severe disabilities because their students most often take an alternate assessment (as opposed to the large group assessment), and the results from alternative assessments are not included in value-added models (Buzick & Laitusis, 2010;Sledge & Pazey, 2013). This puts increased importance on the principal walk-through and classroom observation in the evaluation process.…”
Section: Implications For Research and Practicementioning
confidence: 99%
“…Many researchers have noted concerns with value-added models for evaluating special education teachers in general (Buzick & Laitusis, 2010;Goe, Bell, & Little, 2008;Steinbrecher, Selig, Cosbey, & Thorstensen, 2014). This is particularly problematic for teachers of students with severe disabilities because their students most often take an alternate assessment (as opposed to the large group assessment), and the results from alternative assessments are not included in value-added models (Buzick & Laitusis, 2010;Sledge & Pazey, 2013). This puts increased importance on the principal walk-through and classroom observation in the evaluation process.…”
Section: Implications For Research and Practicementioning
confidence: 99%
“…However, still unanswered is how growth will be defined. Specific issues related to the measurement of special education growth are as follows: (a) What is a reasonable rate of growth for students, (b) the impact of testing accommodations on student performance, (c) the impact of test difficulty, and (d) the longitudinal characteristics of the population of SWD (Buzick & Laitusis, 2010). Similarly, a third type of measure based on student outcomes is the Student Learning Objective (SLO).…”
Section: Student Outcomes Based Teacher Evaluation Modelsmentioning
confidence: 99%
“…As a result of current reform efforts, measures of student growth and teacher observations are the primary approaches to teacher evaluation in current use (Darling-Hammond, 2010; Goe & Croft, 2009; Goe & Holdheide, 2011; Jones, Buzick, & Turkan, 2013). Despite these changes in teacher evaluation requirements, there remains a significant gap of empirical evidence for many of the newer approaches for evaluating teacher effectiveness in relation to non-tested subject areas such as special education (Buzick & Laitusis, 2010; Rockoff & Speroni, 2010; Rothstein, 2010), as some of the larger studies (e.g., MET) have intentionally excluded diverse student groups such as special education due to the measurement challenges they represent (Ho & Kane, 2013; Kane & Cantrell, 2013; Kane & Staiger, 2012). States that do use teacher observation systems often base them on protocols such as Danielson’s Framework for Teaching (FFT).…”
Section: Using Observation Tools For Special Education Teacher Evaluamentioning
confidence: 99%
“…Strategies that allow valid assessments of students in the margins to be made need to be developed (Russell & Kavanaugh, 2011), and careful and complex adaptations of achievement standards may be necessary in order to measure the academic achievement of some students with disabilities (Quenemoen et al, 2010). Researchers are testing various, more accurate models to assess school performance with particular regard to students with disabilities (see, for example, Martineau, 2006;Zvoch & Stevens, 2008;Dunn & Allen, 2009;Buzick & Laitusis, 2010;Drame, 2010). Heck (2006, p. 692) tested different models and concluded that contextual factors had a large impact on school performance estimates, and that the modelling of growth trajectories was the best approach to appreciate school performance, otherwise the comparison between schools would be unfair and blurred by confounding factors.…”
Section: Accountability Presumes Homogeneity But the Student Body Ismentioning
confidence: 99%